THE EMPRISES OF CLUSTERING ILLUSION AS DEPICTED IN GUY DE MAUPASSANT'S THE CHRISTENING - Cahyaningsih Pujimahanani, cahyaningsih; Yuliastuti, Anicleta; Utungga Pasopati, Rommel (TANDA, 2021)
Psychological perspective is widely used today in literary criticism. Guy de Maupassant’s The Christening is one short story related to clustering illusion through the psychological point of view. Clustering illusion is seeing things in logical ways. The question is; how is clustering illusion be depicted in Guy de Maupassant’s The Christening? By using the qualitative method, cultural concepts are used to explain the story in clustering illusion. Things that are so logical then are abandoned in this short story because of religion, custom, and alcohol matters. By comparing the reality and the logic of the doctor as the storyteller, clustering illusion reflects how things that are easily predicted could be really different from reality. Here, tensions between modernity ideas and cultural concepts are contradicted. Modernity which is full of prediction, progress, and individuality is challenged by customary understanding known best by people. In conclusion, the storyteller experiences clustering illusion; what he thinks is logical in an action resulted after another is not as it is because of custom that honors habitual culture above anything else.